Reproductive history and fertility in patients affected by Proteinopathies of the nervous system - Yulemis Sánchez-Machado; Luis Enrique Almaguer Mederos (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: It is known that several proteinopathies of the nervous system are associated with significant changes in reproductive history and fertility. Objective: To show the behavior of reproductive history and fertility in patients with proteinopathies of the nervous system. Material and Methods: A literature review was carried out from January, 2018 to December, 2018. Search was carried out in databases like PubMed, EBSCO, Google Scholar and HighWire.  An advanced search strategy was used in the selection of the articles.  Results: Evidence on the occurrence of significant changes in reproductive history and fertility in patients with proteinopathies of the nervous system were identified. Women with Parkinson´s disease and patients with Amyotrophic Lateral Sclerosis tend to show lower fertility than individuals in the general population. On the contrary, patients with Huntington´s disease or Spinocerebellar Ataxias tend to show higher fertility than individuals in the general population, with a significant role for nuptiality. On the other hand, women with Alzheimer´s disease usually show menopause at older ages whereas women with Parkinson´s disease usually show delayed menarche and a more reduced number of abortions than women in the general population. Conclusions: Available evidence regarding significant changes in the reproductive history and fertility in patients with proteinopathies of the nervous system are frequently contradictory and focused on biological factors with underestimation of socio-economic and cultural factors. Keywords: fertility, nuptiality, proteinopathy, reproductive history